Transforming Sang Kancil Folktale Into Visual Art With Autoethnography - Zuriati Mohamed Shaari; Noor Hidawati Mohamed Amin; Wan Samiati Andriana WMD; Fariz Azmir Mohd Ghazali (LITERACY : International Scientific Journals of Social, Education, Humanities, 2023)
This practice-based research has produced visual art, particularly drawings based on significant animal folktale observations. Folktales symbolize human behavior and culture. Malays use folktales to educate, advise, and satirize. The study covers Dewan Bahasa dan Pustaka's (2015) traditional literary script, Sang Kancil Membilang Buaya. Chang (2008) autoethnography guided artwork development. Visual artists preserved folktales by adding aesthetic appeal and fresh knowledge to Sang Kancil tales. The transmission mechanism provided value by showing visual art with digital presentations without changing the story. This research analyses textual and visual data on Sang Kancil Membilang Buaya through artworks to increase cultural knowledge and awareness of oral tradition and participation among society, in accordance with UNESCO's goals to preserve the intangible heritage.